Evolving genomic landscape of pediatric pneumococcus in two Canadian urban centers following conjugate vaccination - Teatero, Sarah; McGeer, Allison; Plevneshi, Agron; Ricketson, Leah J.; Kellner, James D.; Fittipaldi, Nahuel (Frontiers in Microbiology, 2025)
Background and aimPneumococcal conjugate vaccines (PCVs) have significantly reduced pediatric invasive pneumococcal disease (IPD). However, vaccine escape variants, the emergence of non-vaccine serotypes (NVTs), and antimicrobial resistance (AMR) remain ongoing concerns. We aimed to characterize long-term trends in serotype distribution, lineage composition, and AMR patterns among pediatric IPD cases following PCV introduction in two major Canadian urban centers: Calgary, Alberta, and Toronto, Ontario.MethodsWe combined whole-genome sequencing with epidemiologic data from 818 pediatric IPD isolates collected through population-based, active surveillance in Calgary (1998–2016) and Toronto (2009–2016). Phylogenetic analyses, serotype characterization, and AMR profiling were performed to assess temporal trends across three vaccine eras.ResultsPCV implementation reduced vaccine type serotypes but was followed by expansion of NVTs, including serotypes 22F, 33F, and 15B, with regional differences in prevalence. Serotypes 19A and 3 persisted despite PCV13 inclusion. Several pre-vaccine-associated lineages re-emerged under NVT capsules, indicating capsular switching. Macrolide resistance increased in Calgary (7.4–29.3%), distributed across multiple lineages; penicillin resistance remained infrequent.ConclusionOur findings highlight sustained pneumococcal adaptation through serotype replacement, vaccine escape, and AMR dissemination. Ongoing genomic surveillance is essential to monitor these trends and inform vaccination policies.